Long-Term Patency and Fluid Dynamics of Recipient Artery after End-to-Side Anastomosis for Free Tissue Transfer. Issue 5 (November 2021) - Treiser, Matthew D.; Miles, Megan R.; Albino, Frank P.; Giladi, Aviram M.; Katz, Ryan D.; Higgins, James P.
Abstract : Background: End-to-end microvascular anastomoses sacrifice downstream inline perfusion of the recipient vessels. End-to-side anastomoses, in theory, maintain distal inline flow of the recipient vessel. The proposed benefit of the end-to-side technique depends on patency of the distal vessels and subsequent flow parameters, but maintenance of distal perfusion has not been conclusively demonstrated. Methods: Fifteen patients who underwent a successful extremity free flap procedure via end-to-side anastomoses to a noncritical vessel between 2003 and 2017 were enrolled. Recipient artery patency distal to the anastomosis was assessed using pulse volume recordings and duplex ultrasound imaging. Resistance indices, flow velocities, vessel diameters, volumetric flow, and turbulent flow dimensionless number (Reynolds number) were measured. Comparisons were made to the ipsilateral collateral vessel as well as to the vessels on the nonoperative contralateral limb using paired t tests. Results: Downstream flow was identified in 14 of 15 patients (93 percent patency). There was no statistical difference in resistive indices comparing the anastomotic vessel (0.859 ± 0.300) and the collateral vessel (0.853 ± 0.179) of the ipsilateral extremity. Ultrasound flows were similar; the anastomotic vessel demonstrated downstream volumetric flows of 139 ± 92.0 cm 3 /min versus 137 ± 41.6 cm 3 /min within the same vessel of the nonoperative contralateral limb. The anastomotic vessel had Reynolds numbers well below the turbulent threshold (448 ± 202 and 493 ± 127 for the anastomotic and nonoperative contralateral limb, respectively). Conclusion: End-to-side anastomosis to noncritical vessels resulted in a 93 percent long-term recipient vessel patency rate, with no statistically significant changes in volumetric flows, resistive indices, or fluid dynamics in the vessels that remained patent.